Pod surface characteristics in wild and cultivated Vigna species and resistance to the coreid bug Clavigralla tomentosicollis Stal. (Hemiptera: Coreidae) - Koon, P.; Osisanya, E.O.; Jackai, L.E.N.; Tamo, O.; Reeves, J.; Hughes, Jacqueline d'Arros (2002)
Several Vigna species were used to determine the role of pod trichomes and pod toughness in the resistance of cowpea to feeding damage by the coreid bug Clavigralla tomentosicollis Stal. The scanning electron microscopy study revealed the presence of glandular and non-glandular trichomes on the pod wall of all test genotypes. The cultivated genotypes TVu 1890, TVu 3354 and IT84S-2246 of the V. unguiculata ssp. unguiculata showed significantly lower (P<0.05) densities of glandular trichomes than accessions of the wild Vigna species (TVnu 72, TVnu 151, and TVnu 707). All pods were similar with respect to the density and length of non-glandular trichomes. The two wild accessions TVnu 151 and TVnu 707 of the V. unguiculatassp. dekindtiana had low pod, strength similar to that of the susceptible genotype IT84S-2246, and also showed high seed damage levels comparable to that of this susceptible genotype. These accessions of the subspecies dekindtiana contrasted with the wild and resistant accession TVnu 72 of the V. vexillata species which suffered minor genotypes damage in spite of its low pod strength. The association between high pod strength and low seed damage was found only in the two cultivated genotypes TVu 1890 and TVu 3354. Our results suggest that tough pod wall and high density of glandular trichomes can be combined to achieve enhanced resistance to C. tomentosicollis in cultivated Vigna genotypes.